2019
DOI: 10.1002/gcc.22786
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analyses supporting colorectal, gastric, and prostate cancer syndromes

Abstract: Colorectal cancer (CRC), prostate cancer (PrC), and gastric cancer (GC) are common worldwide, and the incidence is to a certain extent dependent on genetics. We have recently shown that in families with more than one case of CRC, the risk of other malignancies is increased. We therefore suggested the presence of not yet described CRC syndromes. In this study, we have searched for genetic susceptibility loci for potential cancer syndromes involving CRC combined with PrC and/or GC. We have performed SNP (single‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Wallander et al [ 47 ] aimed to identify potential SNPs in patients with CRC, gastric cancer, or PCa. A total of 45 families with at least two members with CRC and at least one with PCa or gastric cancer were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wallander et al [ 47 ] aimed to identify potential SNPs in patients with CRC, gastric cancer, or PCa. A total of 45 families with at least two members with CRC and at least one with PCa or gastric cancer were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Families with both LS and polyposis syndrome in their history were excluded. The linkage analysis identified five potential loci for concordant SNPs, but further assessment of the exome did not reveal any potential pathologic sequence [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously used the Swedish population to search for cancer risk loci and could show higher odds ratios compared with previous GWAS. [24][25][26][27] We then used haplotype analysis as well as single nucleotide polymorphism (SNP) analysis and it was clear that when a founder haplotype was associated with risk, the OR was often higher than any SNP at that locus. We concluded that a haplotype could be better to define individuals at risk compared with SNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, haplotype analysis did suggest that, sometimes, more than one risk factor could be involved at the same risk locus to influence risk. [24][25][26][27] To search for Swedish CRC risk haplotypes, samples from the Swedish Low-risk Colorectal Cancer Study were used. 28 The samples were included and genotyped within the CORECT consortium.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that the immune system plays a vital role in cancer occurrence and development [ 9 ]. Several studies have described a potential association between gene expression and the development of GC [ 10 , 11 , 12 ]. However, there has been no signature to systematically assess immune-relevant genes and predict the prognosis of patients with GC.…”
Section: Introductionmentioning
confidence: 99%